Atypical Findings of Guillain-Barré Syndrome in Children - KARIMZADEH, Parvaneh; BAKHSHANDEH BALI, Mohammadkazem; Nasehi, Mohammad Mahdi; Taheri Otaghsara, Seyedeh Mohaddese; Ghofrani, Mohammad (Iranian Journal of Child Neurology, 2013)
How to cite this article: Karimzadeh P, Bakhshandeh Bali MK, Nasehi MM, Taheri Otaghsara SM, Ghofrani M. Atypical Findings of Guillain-Barré Syndrome in Children. Iran J Child Neurol Autumn 2012;6(4):17-22. Abstract Objective Guillain-Barre syndrome (GBS) is an immune-mediated polyneuropathy that occurs mostly after prior infection. The diagnosis of this syndrome is dependent heavily on the history and examination, although cerebrospinal ﬂuid analysis and electrodiagnostic testing usually confirm the diagnosis. This is a retrospective study which was performed to investigate the atypical features of GBS. Materials & Methods Thirty three patients (21/63.6% males and 12/36.4% females) with GBS were retrospectively studied and prospectively evaluated at the Child Neurology institute of Mofid Children Hospital of Shahid Beheshti University of Medical Sciences between May 2011 and September 2012. Results The mean age was 5.4 years (range, 1.5-10.5).Twenty one patients (87.9 %) had previous history of infections. Eight patients (24.2%) admitted with atypical symptoms like upper limb weakness (3%), ptosis (3%), neck stiffness (3%), inability to stand (proximal weakness) (9.1%), headache (3%) and dysphagia (3%).According to disease process, weakness was ascending in 26 (78.8%), descending in 5 (15.2%) and static in 2 (6.1%) patients. Cranial nerve involvement was found in 8(24.3%) children, most commonly as facial palsy in 3 (9.1%). Conclusion In this study, 24.3% of our patients presented with atypical symptoms of GBS as upper limb weakness, ptosis, neck stiffness, inability to stand (proximal weakness), headache and dysphagia References: Hughes RA, Cornblath DR. Guillain-Barré syndrome. Lancet. 2005 Nov 5;366(9497):1653-66. McGillicuddy DC, Walker O, Shapiro NI, Edlow JA. Guillain-Barré syndrome in the emergency department. Ann Emerg Med. 2006 Apr;47(4):390-3. Cosi V, Versino M. Guillain-Barré syndrome. Neurol Sci. 2006;27(Suppl 1):S47-51. Hughes RA, Cornblath DR. Guillain-Barré syndrome. Lancet. 2005 Nov;366(9497):1653-66. Barzegar M, Dastgiri S, Karegarmaher MH, Varshochiani A. Epidemiology of childhood Guillan Barre syndrome in the north west of Iran. BMC Neurol. 2007 Aug 5;7:22. Vriesendorp FJ, Mishu B, Blaser MJ, Koski CL. Serum antibodies to GM1, GD1b, peripheral nerve myelin, and Campylobacter jejuni in patients with Guillain-Barre syndrome and controls: correlation and prognosis. Ann Neurol. 1993 Aug;34(2):130-5. Asbury AK, Cornblath DR. Assessment of current diagnostic criteria for Guillain-Barre syndrome. Ann Neurol. 1990;27 Suppl:S21-4. Hughes RA, Cornblath DR. Guillain-Barre syndrome. Lancet. 2005 Nov;366(9497):1653-66. Govoni V, Granieri E. Epidemiology of the Guillain-Barre syndrome. Curr Opin Neurol. 2001 Oct;14(5):605-13. Gordon PH, Wilbourn AJ. Early electrodiagnostic findings in Guillain-Barré syndrome. Arch Neurol. 2001 Jun;58(6):913-7. Darabi K, Abdel-Wahab O, Dzik WH. Current usage of intravenous immune globulin and the rationale behind it: the Massachusetts General Hospital data and a review of the literature. Transfusion. 2006 May;46(5):741-53. Hughes RA, Raphaël JC, Swan AV, van Doorn PA. Intravenous immunoglobulin for Guillain-Barré syndrome. Cochrane Database Syst Rev. 2006 Jan 25;(1):CD002063. Hughes RA, Swan AV, van Koningsveld R, van Doorn PA. Corticosteroids for Guillain-Barré syndrome. Cochrane Database Syst Rev. 2006 Apr 19;(2):CD001446. Asbury AK, Cornblath DR. Assessment of Current Diagnostic Criteria for Guillain-Barre syndrome. Ann Neurol. 1990; 27 Suppl:S21-4. van Doorn PA, Ruts L, Jacobs BC. Clinical features, pathogenesis, and treatment of Guillain-Barré syndrome. Lancet Neurol. 2008 Oct;7(10):939-50. Levin KH. Variants and mimics of Guillain-Barré Syndrome. Neurologist. 2004 Mar;10(2):61-74. Winer JB. Guillain-Barré syndrome: clinical variants and their pathogenesis. J Neuroimmunol. 2011 Feb;231(1-2):70-2. Susuki K, Koga M, Hirata K, Isogai E, Yuki N. A Guillain-Barré syndrome variant with prominent facial diplegia. J Neurol. 2009 Nov;256(11):1899-905. Jin Park H, Hyang Lee K. Atypical Miller-Fisher Syndrome Presenting as an Isolated Internal Ophthalmoplegia Following Epstein-Barr Virus Infection. J Pediatr Care for review 2012 Mar; 20(1):39-42. Etem Pişkin I, Calık M, Yarımay G, Adresi Y. Neck stiffness in Guillaine-Barre syndrome subsequent to cytomegalovirus Infection. Dicle Med J. 2011;38(1):104-6. Koul R, Chacko A, Ahmed R, Varghese T, Javed H, Al-Lamki Z. Ten year prospective study (clinical spectrum) of childhood Guillain Barré syndrome in the Arabian peninsula: comparison of outcome in patients in the pre and post intravenous immunoglobulin eras. J Child Neurol. 2003;18(11):767-71. Linden V, da Paz JA, Casella EB, Marques-Dias MJ. Guillain-Barré syndrome in children: clinic, laboratorial and epidemiologic study of 61 patients. Arq Neuropsiquiatr. 2010 Feb;68(1):12-7. Winer JB, Hughes RA, Anderson MJ, Jones DM, Kangro H, Watkins RP. A prospective study of acute idiopathic neuropathy: II antecedent events. J Neurol Neurosurg Psychiatry. 1988 May;51(5):613-18. Ho TW, Mishu B, Li CY, Gao CY, Cornblath DR, Griffin JW et al. Guillain-Barre syndrome in northern China. Relationship to Campylobacter jejuni infection and anti-glycolipid antibodies. Brain. 1995 Jun;118(Pt 3):597-605. Bahou YG, Biary N, al Deeb S. Guillain-Barre syndrome: a series observed at Riyadh Armed Forces Hospital. J Neurol. 1996 Feb;243(2):147-52. Cosi V, Versino M. Guillain-Barré syndrome. J Neurol Sci. 2006;27 (Suppl 1):S47-S51. Winer JB. Guillain Barré syndrome. Mol Pathol. 2001 Dec;54(6):381-5. The prognosis and main prognostic indicators of Guillain-Barré syndrome: A multicentre prospective study of 297 patients. The Italian Guillan-Barre Study Group. Brain. 1996 Dec;119(Pt 6):2053-61.